South Korean Modern Culture in the Drama Series â€œJust One Biteâ€ (Semiotics Analysis by Charles Sanders Peirce) - Nurul Fikriyyah Taqwa; Ikhwan M Said; Hamzah Machmoed; Dafirah Dafirah; Fadhliyah Rahmah Muin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The purpose of this study is to analyze and describe the modern cultural values of South Korea which are represented in the drama series "Just One Bite". This drama series is a South Korean drama series that airs on the official PLAYLIST Global YouTube channel and was released in two seasons. The focus of this research is the representation of South Korean cultural values in the modern era. The object of this study is the drama series "Just One Bite" where the writer takes screenshots of various scenes in the drama series. The method used in this study is an inductive qualitative approach with a type of content analysis. Content analysis is used to study storage data in the form of symbols, text, images and so on. The theory used is Charles Sanders Peirce's semiotic theory, namely that signs are divided into symbols, objects, and interpretants. Based on data analysis using Charles Sanders Peirce's semiotic approach, various data were found that represent South Korean cultural values in the modern era in the drama series "Just One Bite". These cultural values include language in the form of naming food, family culture in the form of sharing food, technological advances in the form of instant food, and preserving culture in the form of serving traditional food with modern food.